Direct measurement of riverine particulate organic carbon age structure - Rosenheim, Brad E.; Galy, Valier (Geophysical Research Letters, 2012)
Carbon cycling studies focusing on transport and transformation of terrigenous carbon sources toward marine sedimentary sinks necessitate separation of particulate organic carbon (OC) derived from many different sources and integrated by river systems. Much progress has been made on isolating and characterizing young biologically-formed OC that is still chemically intact, however quantification and characterization of old, refractory rock-bound OC has remained troublesome. Quantification of both endmembers of riverine OC is important to constrain exchanges linking biologic and geologic carbon cycles and regulating atmospheric CO2 and O-2. Here, we constrain petrogenic OC proportions in suspended sediment from the headwaters of the Ganges River in Nepal through direct measurement using ramped pyrolysis radiocarbon analysis. The unique results apportion the biospheric and petrogenic fractions of bulk particulate OC and characterize biospheric OC residence time. Compared to the same treatment of POC from the lower Mississippi-Atchafalaya River system, contrast in age spectra of the Ganges tributary samples illustrates the difference between small mountainous river systems and large integrative ones in terms of the global carbon cycle. Citation: Rosenheim, B. E., and V. Galy (2012), Direct measurement of riverine particulate organic carbon age structure, Geophys. Res. Lett., 39, L19703, doi:10.1029/2012GL052883.
id: 2248; PT: J; TC: 0; UT: WOS:000309605800002